Fast Padé transform accelerated CSI for hyperpolarized MRS - Hansen, E; Kim, S; Miller, J; Geferath, M; Morrell, G; Laustsen, C (Grapho Publications, 2016)
The fast Padé transform (FPT) is a method of spectral analysis that can be used to reconstruct nuclear magnetic resonance spectra from truncated free induction decay signals with superior robustness and spectral resolution compared with conventional Fourier analysis. The aim of this study is to show the utility of FPT in reducing of the scan time required for hyperpolarized 13C chemical shift imaging (CSI) without sacrificing the ability to resolve a full spectrum. Simulations, phantom, and in vivo hyperpolarized [1-13C] pyruvate CSI data were processed with FPT and compared with conventional analysis methods. FPT shows improved stability and spectral resolution on truncated data compared with the fast Fourier transform and shows results that are comparable to those of the model-based fitting methods, enabling a reduction in the needed acquisition time in 13C CSI experiments. Using FPT can reduce the readout length in the spectral dimension by 2-6 times in 13C CSI compared with conventional Fourier analysis without sacrificing the spectral resolution. This increased speed is crucial for 13C CSI because T1 relaxation considerably limits the available scan time. In addition, FPT can also yield direct quantification of metabolite concentration without the additional peak analysis required in conventional Fourier analysis.